Fundamental rights in the regulation of fundamental education: dignity of the human person of the teacher and quality of teaching (Revista Brasileira Multidisciplinar, 2019)
This paper aims to discuss the precarious condition of elementary school teachers in public schools, to the detriment of the State's duty to promote a decent education, based on fundamental principles present in the Constitution of the Republic of 1988 that govern such educational scope, in particular the one referring to the dignity of the human person with respect to the role of the teacher as one of the main agents acting in this context. To do so, it analyzes articles focused on the educational and historical scope, as well as relevant legislation and case studies with theoretical references on doctrine to reflect the relationship between theory and reality. Thus, the work focuses on teaching in Brazil, its implementation from the colonial period to the present day, demonstrating how the transformations in teaching are linked to the political configurations prevailing in certain historical contexts. Still, according to the references, it discusses the presence of the teacher as a fundamental subject in the maintenance of society within the scope of the teaching-learning process, observing its role as a formator of future citizens. Finally, it discusses the existence of norms and principles established in the Federal Constitution of 1988 and other laws, such as the Law of Guidelines and Bases of National Education, allowing to understand how the constitutional principles are disrespected by the politically and culturally precarious situation in which the teachers of the public education network in Brazil.
Keywords: Education; dignity of teachers; Constitutio